The Paris Seamstress - Lester, Natasha 1973- (New York : Forever, 2018)
When Fabienne Bissette attends the annual Met Gala for an exhibit honoring her grandmother Estella, a famed designer, she begins to learn more about her grandmothers past, uncovering a story of tragedy, heartbreak, and secrets.
Keywords: Fashion designers; Fiction; Family secrets; Fiction; New York (N.Y.); Fiction